2017
DOI: 10.1515/prolas-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Growth Variability and Mycelial Compatibility of Botrytis Cinerea Isolates Originated from Apple and Strawberry in Lithuania

Abstract: Botrytis cinerea Pers.:Fr. is a widespread necrotrophic pathogen causing grey mould on many economically important horticultural crops. The variability in various B. cinerea populations is known to be very high. Despite the economic importance, the variability of B. cinerea has not been investigated previously on fruit crops in Lithuania. The aim of the study was to characterise the variability of B. cinerea strains isolated from strawberry and apple in different growth conditions on various agar media and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Furthermore, the genus Neofabraea , although rarely detected in our study, has been found in Japanese quince in other countries [ 16 , 17 , 18 ]. Considering that the aforementioned genera included several well-known fungi species pathogenic to Rosaceae plants [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], it will be important to clarify the composition of these species in Japanese quince.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the genus Neofabraea , although rarely detected in our study, has been found in Japanese quince in other countries [ 16 , 17 , 18 ]. Considering that the aforementioned genera included several well-known fungi species pathogenic to Rosaceae plants [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], it will be important to clarify the composition of these species in Japanese quince.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that B. cinerea demonstrated morphological differences while grown on a different medium [ 24 ], changes of morphological attributes could be expected for isolates grown on a medium with an additional factor—plant extract. Although the B. cinerea isolates complex was highly sensitive to cinnamon extract, only a few isolates showed changed mycelium—even fewer changed the colour of the colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Botrytis cinerea is known to develop fungicide resistance [ 4 , 20 , 21 , 22 ]. This pathogen infects many plant species and causes grey mould [ 23 , 24 , 25 ] during the growth phase and after harvest [ 18 ]. It is responsible for one of the most significant economic losses of horticultural crop production [ 1 , 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing temperatures become more suitable for diseases from warmer agro-climatic zones ). The temperature effect was observed for Botrytis cinerea growth and variability (Rasiukevičiūtė et al 2017). Also, climate change influences the host, pathogen rate and modified pathogen dynamics.…”
Section: The Strawberry and Raspberry Pathogens Under Changing Climatic Conditionsmentioning
confidence: 94%